Tru-cut biopsy of musculoskeletal tumors - a validation study and a cost analysis - Wang, Edward H.M
To determine whether the closed tru-cut core needle biopsy is a good alternative to the traditional open biopsy for musculoskeletal tumors (1) by determining its diagnostic properties (againt a gold standard) and (2) by performing a cost analysis comparing the Tru-cut biopsy against the open biopsy from the point of view of both the patient and the PGH.A review was conducted of all patients subjected to the Tru-cut biopsy by the Orthopedic Tumor Service over a period of 7-1/2 years.Tru-cut biopsy results were compared against an accepted gold standard. Gold standards were either surgical (open biopsies and eventual surgical excisions), or non-surgical (laboratory examinations or follow-up one year later).Cost analysis was performed by comparing average unit costs of both the Tru-cut biopsy and the open biopsy. A further cost comparison was made between the actual number of patients who had undergone the Tru-cut biopsy (including the costs of errors and failures) and the theoretical possibility that all of these patients had undergone the open biopsy.Investigation was carried out at the UP-PGH (a tertiary care university hospital) on patients referred to the UP-musculoskeletal Tumor Unit during the period January 1, 1993 to June 30, 2000. Once inclusion and exclusion criteria were fulfilled, patients were subjected to the Tru-cut biopsy, and appropriate treatment provided based on the Tru-cut reading. A total of 309 patients underwent the Tru-cut procedure, 203 of whom had both a Tru-cut biopsy reading and a gold standard comparison. Validation of the Tru-cut biopsy for determining malignancy was based on these 203 patients. Four (4) patients had inadequate tissue from Tru-cut for diagnosis but had gold standard results. Together with the 203 patients, they formed the basis for the cost analysis of actual cases.Validation study showed the Tru-cut biopsy to have a sensitivity of 0.97, a specificity of 0.94, a positive predictive value of 0.98, a negative predictive value of 0.92, and an overall accuracy of 0.96 in the detection of malignancy in both bone and soft tissue tumors. The likelihood ratio for a result being malignant is 15.6.Cost analysis showed the Tru-cut biopsy to be affordable from the point of view of both the patient and the PGH, costing 3.10 times cheaper than the open biopsy. No untoward incidents were reported over the 7 years on the 309 patients. The Tru-cut biopsy is a valid, affordable, and safe biopsy procedure. We recommend its continued use in the biopsy of musculoskeletal tumor patients presenting to the PGH.